2020
DOI: 10.1021/acs.cgd.0c00126
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrofuran Hydrate Crystal Growth Inhibitor Performance and Mechanism of Quaternary Ammonium and Phosphonium Salts

Abstract: To gain insight into the hydrate crystal growth inhibitor (HCGIs) mechanism, we have studied various quaternary ammonium ionic liquid salts (QAILs) and phosphonium salts for their ability to prevent structure II (sII) hydrate crystal growth. We tested polyvinylpyrrolidone (PVP), polyvinylcaprolactam (PVCap), tetrapropylammonium bromide (TPrAB), tetrabutylammonium bromide (TBAB), tetrapentylammonium bromide (TPeAB), tetrahexylammonium bromide (THexAB), and tetrabutylphosphonium bromide (TBPB) in a tetrahydrofur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 15 publications
(43 reference statements)
3
34
0
Order By: Relevance
“…HCGIs are PVP K-12, K-15, K-30, and K-90. The 0.04 ≤ V <10 μm s –1 range data of PVP-90 are cited from ref . The error bars were calculated from the temperature gradient and the maximum fluctuation of the growth interface shift around the measured point.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HCGIs are PVP K-12, K-15, K-30, and K-90. The 0.04 ≤ V <10 μm s –1 range data of PVP-90 are cited from ref . The error bars were calculated from the temperature gradient and the maximum fluctuation of the growth interface shift around the measured point.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we employed the same experimental methods reported in a previous paper. , This is our own method for evaluating HCGI inhibition performance. For testing, we used a stoichiometric THF–water (THF–17H 2 O) solution prepared from a dehydrated stabilizer-free THF (99.5 wt % purity, Kanto Chemical Co., Japan) and ultrapure water (18.2 MΩ·cm resistivity).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[23] In some cases, video analysis is used to measure the growth rate of the advancing hydrate crystal, and direct observation of clathrate growth was demonstrated. [20,24,33,[25][26][27][28][29][30][31][32] However, these studies were done mainly on polycrystalline samples (with a few exceptions that included millimeter sized crystals [20,28,30] ), making a detailed description of KHI mechanism more difficult to construct. Such a detailed description of ice growth kinetics in the presence of AFPs has unlocked important understanding of AFP-ice interactions.…”
Section: Introductionmentioning
confidence: 99%